2014
DOI: 10.1002/j.1839-4655.2014.tb00315.x
|View full text |Cite
|
Sign up to set email alerts
|

Local therapy facilitators working with children with developmental delay in rural and remote areas of western New South Wales, Australia: the ‘Outback’ service delivery model

Abstract: Australia's dispersed population in rural areas contributes to poor access to therapy services and the inability of the existing rural therapy workforce to meet demand. As a result, rural children with a developmental delay wait a long time for therapy. This paper describes participant perceptions of a therapy facilitation service model that has worked to improve access to therapy for children in these circumstances. The model, given the pseudonym 'Outback', operates in rural and remote areas of western New So… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 16 publications
(22 reference statements)
0
8
0
Order By: Relevance
“…Contextual differences in non‐urban areas were commonly reported as challenges/difficulties for urban services when transplanting or extending services. Multiple articles discussed the challenges of non‐urban geographical features such as distance, remoteness, limited population numbers, and difficulty recruiting staff (e.g., Danzl et al, 2013 ; Dew et al, 2014 ; Gardner et al, 2016 ; MacLachlan, 2010 ; Merchant et al, 2016 ; Morgan et al, 2019 ; Palcu et al, 2020 ; Sullivan et al, 2014 ; Visagie et al, 2013 ; Woods & Cronin, 2018 ). Often, it was the non‐urban geography and population itself that was held responsible for limited service availability.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Contextual differences in non‐urban areas were commonly reported as challenges/difficulties for urban services when transplanting or extending services. Multiple articles discussed the challenges of non‐urban geographical features such as distance, remoteness, limited population numbers, and difficulty recruiting staff (e.g., Danzl et al, 2013 ; Dew et al, 2014 ; Gardner et al, 2016 ; MacLachlan, 2010 ; Merchant et al, 2016 ; Morgan et al, 2019 ; Palcu et al, 2020 ; Sullivan et al, 2014 ; Visagie et al, 2013 ; Woods & Cronin, 2018 ). Often, it was the non‐urban geography and population itself that was held responsible for limited service availability.…”
Section: Resultsmentioning
confidence: 99%
“… Australia's dispersed population in rural areas contributes to poor access to therapy services and the inability of the existing rural therapy workforce to meet demand. (Dew et al, 2014 , p. 309) [Australia] Publications also descibed problems with the rural workforce including insufficient occupational therapists to refer clients to, and sometimes the perceived limitations of a generalist non‐urban workforce (e.g., Burgman et al, 2011 ; Carpenter & Garfinkel, 2019 ; Cason, 2011 ; Merchant et al, 2016 ; Monz et al, 2019 ; Mroz, 2018 ). Further, therapists in non‐urban spaces were described in some articles as deficient in the specialist skills possessed by urban‐based therapists, which necessitated urban service intervention in non‐urban areas (e.g., Danzl et al, 2016 ; Kingston, Judd, et al, 2015 ; McClure et al, 2010 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dew et al . () conducted a case study of the use of therapy facilitators in rural NSW. The authors concluded that appropriately supported therapy facilitators provide a ‘flexible workforce adjunct that expands the reach of therapists into rural and remote communities and enhances service access for children and their families’ (Dew et al 2013a p. 1).…”
Section: Discussionmentioning
confidence: 99%
“…However, the latter response by rural providers could have pronounced consequences for rural people with disability who may be unable to access timely services, considering rural markets may already be “thin” (Carey et al 2017:198), and state government‐funded services may be unavailable (Mavromaras et al 2018). Rural providers can determine the extent of their NDIS participation, although they may also shoulder some responsibility to ensure services are available for rural people with disability (Dew et al 2014; Gallego et al 2015; Dew et al 2016).…”
Section: Framework Of Rural and Remote Healthmentioning
confidence: 99%